ANALISIS KEMAMPUAN PEMAHAMAN KONSEP SISWA KELAS V MIT AL-BAROKAH PADA MATERI PERBANDINGAN - Anim Anim; Chaliza Shabina Pulungan; Nurhikmah Lubis; Gina Yuningsih (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This research is aimed at exploring broadly how fifth grade students at MIT AL BAROKAH Tanjung Balai build conceptual understanding related to comparative material through a qualitative approach that utilizes information collection from conceptual understanding tests and unstructured interviews which are then processed through the stages of data summarization, presentation of findings and final interpretation referring to the thoughts of Miles and Huberman. The results of data processing show that the majority of the 12 fifth grade students at MIT AL BAROKAH show tendencies as described below: (1) The level of mastery of mathematical concepts in the comparison material shows that there are 4 students in the high category, then 2 students are in the medium category and 6 students are in the low category based on the results of mapping their abilities; (2) The level of mathematical concept comprehension ability with detailed indicators of restating a concept related to understanding the relationship between mathematical topics, indicators providing examples and non-examples of mathematical concepts related to applying mathematical concepts to other scientific disciplines, and indicators applying related concepts in everyday life. Keyword: conceptual understanding; comparison; basic education. Abstrak: Penelitian ini diarahkan untuk mengungkap secara mendalam kemampuan pemahaman konsep para siswa kelas V di MIT AL BAROKAH Tanjung Balai mengenai materi perbandingan melalui pendekatan kualitatif yang menghimpun data dari tes pemahaman konsep dan wawancara bebas yang selanjutnya diproses dengan langkah peringkasan penyajian serta simpulan akhir mengikuti gagasan Miles dan Huberman. Temuan proses analisis memperlihatkan bahwa mayoritas dari 12 peserta didik kelas V MIT AL BAROKAH menampakkan kecenderungan sebagaimana dijelaskan berikut: (1) Tingkatan pemahaman konsep matematika dalam materi perbandingan memperlihatkan bahwa ada 4 peserta didik pada tingkatan tinggi kemudian 2 peserta didik pada tingkatan sedang serta 6 peserta didik pada tingkatan rendah setelah dilakukan pemetaan kemampuan; (2) Tingkatan pemahaman konsep matematika meliputi uraian indikator tentang kemampuan menyatakan kembali gagasan matematika yang berhubungan dengan pengenalan relasi antar topik matematika kemudian indikator yang menunjukkan kecakapan memberikan contoh maupun bukan contoh dari konsep matematika yang terkait dengan penerapan konsep dalam berbagai cabang ilmu serta indikator kemampuan mengaplikasikan konsep tersebut dalam kegiatan hidup sehari hari. Kata kunci: pemahaman konsep; perbandingan; pendidikan dasar.